Effects of heat treatment on microstructure and hardness of D2 tools - Hariningsih, Hariningsih; Lutiyatmi, Lutiyatmi; Daryanto, Tri (Universitas Muhammadiyah Surakarta, 2022)
D2 high chromium tool steel is widely used to produce tools and components that work at significant dynamic loads, such as dies, punches and rollers. The steel must have a good combination of strength and toughness, which heat treatment can obtain. Therefore, this study discusses the effect of normalising, hardening, and tempering on the microstructure and hardness of D2 tools. Normalising and hardening were carried out respectively at 1020°C for 30 minutes, followed by rapid cooling using oil. Tempering was realised by reheating the quenched sample at 250°C and 400°C with variations in holding time of 15 minutes, 30 minutes, and 45 minutes. The hardness of the specimens was measured using a Rockwell hardness tester, whereas the microstructure was observed with an optical microscope. The results indicated that the microstructure changes to martensite and carbide after quenching, while the microstructure becomes tempered martensite and carbide after tempering. Normalising and hardening have almost no impact on hardness, and the increase in temperature and holding time causes a decrease in hardness. The reduction in hardness is noticeable for steels tempered to 400 °C and held for 45 minutes.